The Influence of Brand Image and Islamic Fashion Style Orientation on the Competitive Advantage of Erigo Brand Products on Muslim Teenagers in Banyumas Regency - Febrianing, Brina; Susilowati, Dewi; Ulfah, Permata (Islamic Economic Scholar Association and Faculty of Economics and Business Universitas Jenderal Soedirman, 2024)
In this modern era, fashion is evolving at a rapid pace, with high-quality and attractive clothing becoming a favorite of many. Indonesian local fashion brands, such as Erigo, are showing significant growth, not only in the domestic market but also internationally. This is evidenced by Erigo's participation in New York Fashion Week, a prestigious fashion event in the world, as well as its marketing strategy that extends to Time Square in New York, USA, signaling significant progress compared to other brands. Erigo, which is in high demand among young people who are searching for identity and following trends, is the focus of this research. In particular, this study took a sample of teenagers in Banyumas Regency, which is known to have a very large number of students and college students, being at the forefront of the Bralingmascakeb region. In the midst of growing fashion trends, Muslim teenagers are also expected to choose clothes that are in accordance with Islamic law. This study aims to examine the effect of brand image and Islamic fashion style orientation on Erigo's competitive advantage. The research method used is associative with a quantitative approach, using primary data from a questionnaire with a sample size of 150 Muslim teenage respondents in Banyumas Regency. Data analysis involves instrument test, classical assumption test, multiple regression analysis, and hypothesis testing. The results show that both brand image and Islamic fashion style orientation have a positive influence on Erigo's competitive advantage.